PHYTOCHEMICAL AND NUTRITIONAL PROFILING OF INDIGENOUS SOYBEAN VARIETIES; A POTENTIAL PLANT-BASED PROTEIN SOURCE TO ALLEVIATE MALNOURISHMENT - Anila Faiz; Imran Pasha; Muhammad Atif Randhawa; Muhammad Shahid (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Soybean (Glycine max) is an excellent source of plant-based protein with a substantial amount of minerals, fatty acids, and some therapeutic substances such as isoflavones, flavonoids, etc. Many people in developing countries suffer from protein-energy malnourishment due to the unavailability of a balanced diet or lack of protein in food. Several Pakistani soybean varieties have been introduced, but their use as food is not very common as people are concerned about their characteristics and quality. Hence, in this study, native soybean varieties were studied for nutritional quality to assess their potential as food sources. Eight different Pakistani Soybean varieties were assessed for their nutritional aspects including chemical composition, mineral content, free radical activity, amino acid assay, and fatty acid profile. Statistical analysis was performed to analyze the level of significance. The protein content for all the varieties was seen within the range of 36% to 43%. Amino acid analysis showed an appreciable profile with a good amount of all the essential amino acids. Moreover, the fatty acid profile showed the highest value of oleic acid and linoleic acid in V5 (Malakand-96) and V8 (Swat-84) at 15.590% and 59.863% respectively. However, for linolenic, palmitic, and stearic acid, the highest value was seen for V1 (Ajmeri) at 7.066%, 14.677%, and 5.190% respectively. Overall, findings suggested that all the varieties have a satisfactory nutritional profile with the potential to be used as an effective source of plant-based protein to combat the increasing protein demand and meet the nutritional needs of people.